Comparing Iranian and Duke University\'s Master of Nursing Education Programs in Geriatrics: A Comparative Study - Hamideh Mancheri; Gholam Reza Mahmoodi-Shan; Leila Jouybari; Malihe Kabusi (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: To identify the strengths and weaknesses of the curriculum and improve the quality of education in the Master of Nursing in Geriatrics, this study aimed to compare the educational program of the Master of Nursing in Geriatrics at Golestan University of Medical Sciences in Iran and Duke University in the United States. Methods: This is a descriptive comparative study. Information on the Master of Nursing in Geriatrics curriculum was extracted through documents available on the electronic pages of the two universities in 2024 and by searching related articles using  following keywords: “Gerontological nursing,” “Master's degree,” “Comparative study,” “Curriculum,”  “Duke University,” and “Iran as well as equivalent of these words in persian.” In this review, the curriculum of the Master of Nursing in Geriatrics was analyzed in terms of history, definition, philosophy, mission and vision, the objective of the educational program, student admission, method of presentation and duration of the educational course, number of course units, position and role of graduates in four stages of description, interpretation, juxtaposition, and comparison using the Bereday method. Results: Duke's Master of Nursing in Geriatrics program has a longer history and duration of study. Duke University offers the Master of Nursing in Geriatrics as two acute and primary care programs; however, it is being offered through one program in Iran. At Duke University, student entry criteria are different and based on the quality of candidates. The vision of Duke University focuses on globalization, while the vision of this field in Iran has a national and regional perspective. In Iran, the course is offered in  person and full- time, whereas at Duke University, it is offered full-time and part-time and online and in person. Conclusion: Considering issues such as the use of a decentralized method and multiple criteria for student admission, the existence of part-time distance learning courses and online classes, the presence of an instructor familiar with the field of geriatrics, and the presence of an appropriate clinical environment can strengthen the curriculum of the master's degree in geriatric nursing in Iran.